Chemo‐Mechanical Coupling in Fractured Shale With Water and Hydrocarbon Flow. Issue 5 (9th March 2021) - Wenning, Quinn C.; Madonna, Claudio; Kurotori, Takeshi; Petrini, Claudio; Hwang, Junyoung; Zappone, Alba; Wiemer, Stefan; Giardini, Domenico; Pini, Ronny
Abstract: The transport of chemically reactive fluids through fractured clay‐rich rocks is fundamental to many subsurface engineering technologies. Here, we present results of direct‐shear laboratory experiments with simultaneous imaging by X‐ray Computed Tomography in Opalinus claystone with subsequent fluid injection to unravel the interplay between mechanical fracture deformation, fluid sorption, and flow. Under constant radial stress ( σ c = 1.5 MPa), the average mechanical aperture d ¯ C T increases with shear displacement. Upon brine injection, d ¯ C T is reduced by 40% relative to initial conditions ( d ¯ C T 0 = 140 − 250 μ m) and fluid‐sorption induces a divergent displacement of the two sample halves (Δ h = ±50 − 170 μ m) quantified by digital image correlation. None of these changes are observed in a control experiment with decane, indicating that creep is subordinate to swelling in sealing the fracture. Swelling‐induced changes in permeability within the fracture are heterogeneous and largely affect the fracture flow field, as computed using numerical simulations. Plain Language Summary: Our current energy supply largely depends on the ability to exploit the subsurface. Examples include petroleum extraction, geothermal energy, and geologic CO2 storage. Fractures are widely present in the subsurface but can also be induced through the forced injection and/or withdrawal of fluids. Quantifying the ability (or lack thereof) of fractures to transport fluids is of increasing importance for the safe operation of these technologies. Here, we have developed an experimental method to directly observe the behavior of a fractured claystone undergoing geomechanical damage followed by fluid re‐saturation. Depending on the fluid, a self‐sealing process can be initiated (brine), whereby the fracture effectively closes, or prevented (decane), providing a means to further engineer and control the behavior of fractured media. Key Points: Three‐dimensional fracture aperture maps are generated by X‐ray Computed Tomography during shearing and fluid injection A self‐sealing process within the fracture can be initiated (brine) or prevented (decane) Creep is subordinate to swelling at conditions of low confining stress